2019
DOI: 10.1182/blood.2018874859
|View full text |Cite
|
Sign up to set email alerts
|

Plasmin-mediated fibrinolysis enables macrophage migration in a murine model of inflammation

Abstract: Efficient migration of macrophages to sites of inflammation requires cell surface–bound plasmin(ogen). Here, we investigated the mechanisms underlying the deficits of plasmin(ogen)-mediated macrophage migration in 2 models: murine thioglycollate-induced peritonitis and in vitro macrophage migration. As previously reported, macrophage migration into the peritoneal cavity of mice in response to thioglycollate was significantly impaired in the absence of plasminogen. Fibrin(ogen) deposition was noted in the perit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 53 publications
(84 reference statements)
1
31
0
Order By: Relevance
“…In some cases, plasminogen depletion in mouse models of inflammation leads to a reduction in inflammatory signals. However, in many instances, this function of plasminogen is dependent on fibrin and fibrinolysis, with plasminogen regulating inflammatory signals only when fibrin is present (Berri et al, 2013; Silva et al, 2019; Raghu et al, 2014; De Nardo et al, 2010; Jennewein et al, 2011). These instances are discussed in more detail below.…”
Section: Plasminogen Has a Variety Of Functions That Lead To Inflammatory Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, plasminogen depletion in mouse models of inflammation leads to a reduction in inflammatory signals. However, in many instances, this function of plasminogen is dependent on fibrin and fibrinolysis, with plasminogen regulating inflammatory signals only when fibrin is present (Berri et al, 2013; Silva et al, 2019; Raghu et al, 2014; De Nardo et al, 2010; Jennewein et al, 2011). These instances are discussed in more detail below.…”
Section: Plasminogen Has a Variety Of Functions That Lead To Inflammatory Regulationmentioning
confidence: 99%
“…Many of plasminogen’s roles in inflammation can also be mechanistically linked to fibrin, which has its own role driving an inflammatory response (Davalos and Akassoglou, 2012; Flick et al, 2004). For example, in Plg −/− mice there is reduced monocyte, macrophage, and dendritic cell recruitment into the peritoneal cavity in a thioglycollate-induced peritonitis model (Silva et al, 2019). Although a previous study (Gong et al, 2008) suggested that this was due to macrophage retention in the peritoneal wall, this more recent study noticed that fibrin accumulated in the peritoneal wall of Plg −/− mice and hypothesized that decreased fibrinolysis by plasminogen contributed to the decreased monocytic cell migration.…”
Section: Plasminogen Has a Variety Of Functions That Lead To Inflammatory Regulationmentioning
confidence: 99%
“…As a broad-spectrum protease, PLG has many physiological functions, and it is understood that PLG interacts with cell surfaces for many of these roles. PLG, considered a proinflammatory cell activator, is a potent chemoattractant for monocytes, macrophages, and dendritic cells [13, 14]. There is also evidence that PLG plays a role in innate immunity by regulating macrophage phagocytosis [15] and can affect inflammatory cell function through the production of cytokines, reactive oxygen species, and other inflammatory mediators [16].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, plasmin increases phagocytosis but inhibits production of inflammatory cytokines and cell migration in dendritic cells, providing an alternative proreparative, anti‐inflammatory effect of plasmin on phagocytic cells 63 . However, one recent study demonstrated that fibrinolysis itself enhances macrophage ingress and egress by preventing macrophage tethering to fibrin through α M β 2 binding 64 . In addition, the plasminogen activators t‐PA and urokinase plasminogen activator (u‐PA) bind to the annexin A2/S100A10 heterotetrameric complex and the u‐PA receptor (u‐PAR), respectively, to facilitate activation of plasmin on the surface of macrophages and damaged cells 65‐67 .…”
Section: Plasmin and Fibrin In Skeletal Repairmentioning
confidence: 99%
“…These chronic complications, including the development of muscle fibrosis, muscle calcification, and sarcopenia, can cause significant pain and permanent loss of muscle function in patients 12,76,77 . Animal studies have demonstrated that a plasmin deficiency causes ineffective macrophage infiltration and function, persistent fibrin deposition, and chronic inflammation of injured tissues 57,58,62,64,78 . In a muscle injury specifically, the absence of plasmin results in fibrosis, skeletal muscle calcification, and bone formation within injured muscle, better known as heterotopic ossification (HO) (Figure 2B).…”
Section: Plasmin and Fibrin In Muscle Repairmentioning
confidence: 99%